THE INFLUENCE OF CLASSROOM COMMUNICATION ON STUDENT COMMITMENT TO THE UNIVERSITY - Kareva, Veronika (European Scientific Journal, ESJ, 2014)
In today’s competitive world in which we witness how much effort people put in selling goods or services to others, education has become a business, too. Macedonia seems to follow this world trend in education. The number of universities has increased tremendously in the last 10 years. This means that universities have to struggle to attract students. While advertising their services, universities can use all the resources that are available to them: good facilities, attractive campuses, use of technology in the educational process, attractive study programs. But the critical component for the perception about the quality that people have about a particular university still appears to be a classroom and teachers. This paper aims to find out if there is a relationship between classroom communication and the commitment of students to their university. To be more precise, how efficient classroom communication can create positive emotions towards the university which on the other side has consequences on the way students feel about their university, how they present it to others and how they will relate to it in the future as members of the community in which it exists.